GOVERNANCE EVALUATION ELECTRONIC SECURITY SYSTEM (ESS) (Case Study: ABC Central Bank) - Aziz, RZ Abdul; Ikhsanudin, Anas; Hasibuan, M Said (Sinkron : jurnal dan penelitian teknik informatika, 2024)
As we know, the role of the security system has a very important role for a state institution to provide security and comfort in carrying out its functions, such as the ABC central bank. A good security system is a security system that is supported by a reliable electronic security system and is composed of several components such as a CCTV monitoring system, Access Control System (ACS), Security Alarm System (SAS), and Fire Alarm System (FAS). This system is very necessary to provide support for the duties of these state institutions to protect devices, data and electronic infrastructure from potential threats and security risks. The main functions of electronic security systems include prevention, detection, response to incidents, and recovery after disturbances/disasters. For this reason, efforts are needed to provide an evaluation of the system maturity level and information security management as a form of risk management to maintain the continuity of system use. This research uses the INDEKS KAMI 4.1 to map ESS governance maturity and the OCTAVE Allegro method to analyze information security management. From the analysis carried out, it has been concluded that the ESS implementation has been operated well in accordance with the security system requirements and has reached a good level of governance maturity. Information security management analysis carried out using the OCTAVE Allegro method has succeeded in identifying information security management with the result that information security management has been implemented well. This is proven by the existence of indicators, namely CCTV recording data, log systems as information assets that have been managed and distributed according to authority